Editors’ note: On Community, Collaboration, and Difference - Harmony Bench; Simon Ellis (The International Journal of Screendance, 2015)
No abstract available
Keywords: community; communities; collaboration; difference; other; open source; International Journal of Screendance; care; support; volume 5